2006
DOI: 10.1007/s11207-006-1831-5
|View full text |Cite
|
Sign up to set email alerts
|

YOHKOH/WBS Recalibration and a Comprehensive Catalogue of Solar Flares Observed by YOHKOH SXT, HXT and WBS Instruments

Abstract: The flare catalogue of the Yohkoh mission is compiled and linked to this article as an electronic supplement. For showing flare characteristics over wide energy range concisely, we provide the images of Hard X-ray Telescope (HXT) and the Soft X-ray Telescope (SXT), and the spectra of Hard X-ray Spectrometer (HXS) and Gamma-Ray Spectrometer (GRS) with the Wide Band Spectrometer (WBS) time profiles. The energy versus pulse height (PH) data channels in HXS and GRS are re-calibrated by using the data of the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
1
14
1
Order By: Relevance
“…An SXR feature connects microwave sources 1 and 3. The brightest spots in hard and soft X-ray images coincide, as the catalog by Sato et al (2006) shows. Figure 4b shows the localization of sources of subsecond pulses (see also Figures 4 and 5 in Altyntsev et al, 2003).…”
Section: Observationsmentioning
confidence: 56%
“…An SXR feature connects microwave sources 1 and 3. The brightest spots in hard and soft X-ray images coincide, as the catalog by Sato et al (2006) shows. Figure 4b shows the localization of sources of subsecond pulses (see also Figures 4 and 5 in Altyntsev et al, 2003).…”
Section: Observationsmentioning
confidence: 56%
“…Most of the flares are at the limb and very little looplike structure can be discerned in the data. Ten of the flares are included in the Sato et al (1993) catalog of flares observed with the Yohkoh SXT and Hard X-Ray Telescope (HXT). The images in the catalog made from the HXT data generally show only one emitting feature-again making it difficult to determine loop size parameters.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Yohkoh Hard X-ray Telescope Flare Catalogue (Sato et al, 2006) and selected a set of flares that had at least three distinct pulses on the HXR light curve and for which at least 10 HXT images could be reconstructed with satisfactory accuracy. To analyze plasma properties of the selected flares we used the Yohkoh Soft X-ray Telescope (SXT; Tsuneta et al, 1991) images obtained with the Be119 and Al12 filters.…”
Section: Observations and Resultsmentioning
confidence: 99%